Morphometric differentiation of Pseudocalanus minutus populations in the Barents Sea. - Dvoretsky, V.G. & A.G. Dvoretsky (Acta Zoologica, 2013)
We investigated spatial variations in the morphometric characteristics (total length of body, lengths of cephalothorax, abdomen and antennules, and their relative proportions) of Pseudocalanus minutus, an abundant copepod species across the Barents Sea in August–September 2007. Females were found to have higher values for the measured parameters than males. The average absolute morphometric characters of both sexes increased from the south to the north. In most cases, parameters were similar in the southern, central, and eastern regions delineated by cluster analyses of oceanographic variables. The morphometric characteristics were strongly correlated with environmental variables in both males and females. Multiple regression analysis showed that temperature together with salinity explained 72–85% (in females) and 38–91% (in males) of the total variations in the log10 -transformed morphometric parameters. According to principal component analysis and discriminant function analysis, two distinct groups could be separated in the Barents Sea. The ﬁrst group included the copepods from the northern region; the other included populations from the southern, central, and eastern regions. The observed morphological variation can be interpreted as geographical variation connected with hydrological variability.